2019
DOI: 10.3390/coatings9040243
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Failure of Composite Coatings due to Thermal and Hygroscopic Stresses

Abstract: Due to the higher thermal and moisture expansions of epoxy coatings than the rigid substrate, these coatings suffer from high thermal and hygroscopic stresses, leading to coating/substrate interfacial crack growth. Herein, a parametric study was conducted systematically on epoxy coatings incorporated with fillers, in order to understand their effects on coating/substrate interface delamination caused by thermal and hygroscopic stresses. A finite element model (FEM) was developed to determine an indicator J-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…Hardness of the coating can be in the range from 5 GPa for Ti 11 Mg 29 Gd 2 N 58 coating to 45 GPa for CrCN/CrN coating with 1 µm thick layer of tetrahedral carbon [10,11]. However, this method also allows producing reflective coatings, e.g., Nb 2 O 5 /SiO 2 coating, with a hardness even lower than 1 GPa [12]. Coatings of high hardness are mainly used 2 of 34 for anti-wear applications, as protective coatings for tools and knives [13,14], and for anti-erosion applications [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Hardness of the coating can be in the range from 5 GPa for Ti 11 Mg 29 Gd 2 N 58 coating to 45 GPa for CrCN/CrN coating with 1 µm thick layer of tetrahedral carbon [10,11]. However, this method also allows producing reflective coatings, e.g., Nb 2 O 5 /SiO 2 coating, with a hardness even lower than 1 GPa [12]. Coatings of high hardness are mainly used 2 of 34 for anti-wear applications, as protective coatings for tools and knives [13,14], and for anti-erosion applications [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…CFRP has good, long-lasting performance, in general, but it is still sensitive to humidity and heat [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. With the addition of humidity, heat, and other factors, the mechanical and thermal properties of the material could be reduced, which affects its life.…”
Section: Introductionmentioning
confidence: 99%
“…The permeation behavior of water and gas through the polymer/aluminum coating has also been investigated to achieve a detailed understanding of its mechanical performance under thermal and/or hygroscopic stresses [ 27 ]. Recently, the effects of epoxy composite coatings on interface delamination due to thermal and hygroscopic stresses have also been analyzed using FE simulations and compared with experimental results [ 28 ]. It was suggested that the interfacial debonding or failure originated from the thermal or hygroscopic stress that tends to take place due to the mismatch in thermal or moisture expansion between the epoxy resin matrix and the fiber reinforcements [ 17 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these methods require a relatively long time to detect all the cracks in coatings. Currently, the detection of surface cracks in coatings is still a research hot spot in the nondestructive testing field [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%